Principles of internet marketing - Hanson, Ward A. (Cincinnati, OH : South-Western College, 2000)
This book is divided into three parts: Framework for internet marketing; Online marketing themes; and Implementation and organization.
Keywords: Marketing; Internet marketing; Internet marketing